GAMBARAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PERAWAT - Novianti, Devi; Dwi Rahayu, Indah; Ariyanti, Sri (Literasi Intelektual, 2024)
Background: Healthcare-Associated Infections (HAIs) significantly contribute to morbidity and mortality, with emotional, financial, and medical consequences. Approximately one in 25 inpatients per year experiences infections related to hospital care, leading to death and increased healthcare costs. The use of Personal Protective Equipment (PPE) by healthcare workers aims to protect themselves and patients from exposure to pathogenic microbes. However, the compliance level of nurses in using PPE is still suboptimal. Objective: This study aims to provide an overview of the compliance level of nurses in using PPE in the isolation room of Dr. Soedarso Hospital in Pontianak Methods: This study employs a descriptive approach to illustrate nurses' compliance in using PPE in the isolation room of Dr. Soedarso Hospital in Pontianak. The sampling technique involves total sampling with a purposive sampling approach, with a sample size of 30 nurses working in the isolation room. Results: The study reveals that the majority of respondents are aged between 26 and 35 years, predominantly female, hold a D3 nursing degree, and have work experience of over 13 years. Most respondents demonstrate good compliance in using PPE while working in the isolation room of Dr. Soedarso Hospital in Pontianak. Conclusion: The research concludes that the majority of nurses in the isolation room of Dr. Soedarso Hospital in Pontianak comply with PPE usage, indicating adequate awareness and adherence to safety practices while providing healthcare services in the hospital environment.